2023
DOI: 10.1007/s11250-023-03547-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage periods and SPIDES on embryonic mortality, hatching characteristics, and quality of newly hatched chicks in broiler eggs

Abstract: AbstractsEgg storage duration can affect embryo mortality, hatching characteristics, hatching time, and post-hatch chick quality. In order to assess these effects, the impact of storage duration (5 days, 10 days, 15 days) and short incubation period during egg storage (SPIDES) investigated further 18, 900 eggs of broiler breeder (ROSS 308) in 3 × 2 factorial arrangement design. In the SPIDES treatment, the egg shell temperature was raised from its storage temperature (18 °C) and held at 100 °F for 3.5 h. Stora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…These findings agreed with the previous reports of Okasha et al [26] who reported reduction in hatchability % for eggs stored for long period (15 days). They ascribed the low hatchability % following the long storage to increasing embryonic death with the long-term egg preservation.…”
Section: Effect Of Storage Period Frequent Spides and Chicken Breed O...supporting
confidence: 94%
See 2 more Smart Citations
“…These findings agreed with the previous reports of Okasha et al [26] who reported reduction in hatchability % for eggs stored for long period (15 days). They ascribed the low hatchability % following the long storage to increasing embryonic death with the long-term egg preservation.…”
Section: Effect Of Storage Period Frequent Spides and Chicken Breed O...supporting
confidence: 94%
“…The high body weights following the long term egg preservation agreed with the findings of Nowaczewski et al [25] which recorded increases of chicks' body weights following the long term egg storage. Again, decreasing the chicks hatching weights following the application of SPIDES may be linked with increasing water loss during long term storage [26]. Also, the heavy weights in the case of Avian-34 compared to Fayoumi were perhaps correlated to the differences in egg weight between the two breeds hence there is a positive correlation between egg weight and chick's weight.…”
Section: Post-hatching Performance Following Different Spides Conditionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Egg weight loss is a quantitative trait that is affected not only by the eggshell characteristics and hen genotype (strain), but also by surrounding environmental conditions (such as temperature and RH), as well as the egg management (such as the preincubation egg storage) ( Khalil et al, 2016 ; Grochowska et al, 2019 ; Okasha et al, 2023 ). The proportion of egg weight loss is crucial for ensuring enough air cell size inside the egg for proper lung function and chick pipping ( Ar and Rahn, 1980 ).…”
Section: Discussionmentioning
confidence: 99%